Les grammaires de construction - Jérôme Puckica (Anglophonia)
This paper is a short presentation of some basic aspects of the grammatical theory known as construction grammar, which has been differently developed by Ch. Fillmore, R. Langacker, and A. Goldberg, among others. First, the notion of “construction” as a form-meaning pairing is explained, as well as the different types of constructions recognized in the theory (simple v. complex, specified or substantive v. schematic or formal). Then, some of the fundamental postulates of the theory are exposed : the conception of a native speaker’s grammatical knowledge as a network of constructions, the lexicon-grammar continuum, the operation of unification involved in the production of sentences, the non-derivational and monostratal nature of construction grammar, and the usage-based approach to language acquisition that is shared by most constructionists. Finally, it is shown that “verbo-centric” approaches to verbal clauses, including that of generative grammar based on the Projection Principle, cannot provide a satisfying treatment of cases of multiple argument realisation, while these are elegantly and economically accountedfor within the constructionist framework.